Pemanfaatan Air Kelapa Sebagai Biostimulan Alami Untuk Mempercepat Perkecambahan Benih Cabai Merah Besar (Capsicum Annum) Di Rooftop - Dencervis Gulo (CV. SINAR HOWUHOWU, 2025)
Coconut water is a natural source of plant growth hormones such as auxins, gibberellins, and cytokinins, which have potential as biostimulants in seed germination. This study aimed to examine the effect of coconut water on the germination rate and percentage of large red chili pepper (Capsicum annuum) seeds under limited-space cultivation on a rooftop. The experiment was conducted over 14 days with two treatments: seed soaking in coconut water and plain water (as control), each with three replications of 10 seeds. The results showed that seeds treated with coconut water began germinating on day one and reached 100% germination by day nine. In contrast, seeds soaked in plain water began germinating on day two and reached only 76.67% germination by day fourteen. These findings indicate that coconut water significantly accelerates the onset of germination and improves seed viability. The natural plant growth substances present in coconut water are believed to stimulate physiological processes in seeds, making it an effective, eco-friendly, and accessible biostimulant for small-scale and urban agriculture systems.